The ANALISIS FAKTOR SOSIAL, BUDAYA, PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN DI MODESHOP BALIKPAPAN - Linda, Marlindawaty (Jurnal GeoEkonomi, 2022)
This researchÂ aims toÂ analyzeÂ social,Â cultural, personal and psychologicalÂ variables on purchasing decisions. Method of data collection through the distribution of questionnairesÂ to all consumers who shop at ModeshopÂ BalikpapanÂ as the object of this research. Non probabilityÂ samplingÂ technique with a sample size ofÂ 100 respondents. This type of research is descriptive quantitativeÂ using classical assumption test and multiple linear regression through SPSS.V.20 statistical test tool.Â The resultsÂ of this research, simultaneously social, cultural, personal and psychological variables influence to purchasing decisions at Modeshop Balikpapan and partially, personalÂ Â variables haveÂ a significant and dominant influence on consumer purchasing decisionsÂ atÂ ModeshopÂ Balikpapan.